Perbandingan Pengaruh Senam Yoga Dan Senam Hamil Terhadap Lama Kala I Persalinan Di Puskesmas Cimanggu Kabupaten Pandeglang Banten Tahun 2022: Comparison of the Effect of Yoga Exercises and Pregnancy Exercise on the Length of the First Stage of Childbirth at the Cimanggu Health Center, Pandeglang Regency, Banten in 2022 - Susilawati (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Long labor as one of the causes of maternal death also tends to be quite high. Cimanggu Health Center 2021 found 1 case of maternal death caused by bleeding the cause, namely due to prolonged labor. Various efforts have been made to reduce the number of long labors, one of which is by doing yoga and pregnancy exercises. The purpose of the study was to compare the effect of yoga and pregnancy exercises on the length of the first stage of labor at the Cimanggu Public Health Center, Pandeglang Regency, Banten in 2022.  Methods: The research method was a quasi-experimental design with a post-test-only design with control groups, the number of samples was 60 respondents, and the total sampling technique was total sampling, data analysis using an Independent T-test test.    Result: The results of the study on the length of the first stage of labor in the yoga exercise group obtained an average value = of 8,13; the length of the first stage of labor in the pregnant exercise group obtained an average value = 10,63. The results of the bivariate analysis showed that there was a difference in the effect of yoga and pregnancy exercises on the length of the first stage of labor with a significance level of 0,000.  Discussion: The conclusion of the research is that there is a difference in the effect of yoga and pregnancy exercises on the length of the first stage of labor. Suggestions for health workers, especially midwives, can consider implementing yoga and pregnancy exercises in classes for pregnant women as care to prepare for a safe, and comfortable delivery. It is also recommended to open yoga and pregnancy exercise classes with trained instructors or midwives who have been officially certified in participating in pregnancy exercise training.